- Cut-Off Point Kadar Feritin sebagai Prediktor Kadar NLR pada Pasien Talasemia Beta Mayor: - - Tsaqihrafa, Nasyaira; -, -; -, Terza Aflika Happy; -, Dyah Wulan Sumekar Rengganis Wardani (Medula, 2025)
Thalassemia is a hereditary disease that has a high prevalence, both in Indonesia and the world. Thalassemia with the most severe symptoms is the classification of beta thalassemia major. Severe symptoms have an impact on poor body conditions, one of which can occur iron accumulation and inflammation. Thus, in patients with beta thalassemia major, ferritin and neutrophil lymphocyte ratio (NLR) examinations can be carried out. The cutoff point for ferritin levels as a predictor of NLR levels in patients with beta thalassemia major can also be found out. This study used a cross-sectional design, then the data results were processed with a data processing application on a computer. The cutoff value for ferritin levels was 2907.145 ng/mL which can predict NLR levels. The ferritin level used as a predictor was obtained through the cutoff point by analyzing the receiver operating characteristic (ROC) curve in the data processing application and changing its coordinates in the form of a graph. The result was 2907.145 ng/mL where the ferritin level above that can increase the risk of increasing NLR levels in patients with beta thalassemia major.